Synthesis of Biofoam from Cassava Peel Starch, Banana Peel Starch and Chitosan as Additives - Darni, Yuli; Mayanti, Eva; Anandati, Ghea Maulidaco; Ginting, Simparmin Br.; Lismeri, Lia; Nugrahini, Panca; Utami, Herti (Jurnal Bahan Alam Terbarukan, 2023)
Biodegradable Foam (Biofoam) material has been made for application of styrofoam substitute food packaging material from a mixture of starch with chitosan as an additive. The purpose of this study was to determine the effect of molding temperature on biofoam products and to determine the effect of chitosan addition on the physical, mechanical, and biodegrability properties of biofoam made from cassava peel starch (a) and banana peel starch (b) which is close to commercial biofoam standards. The production of biofoam uses variations in molding temperature of 125, 150 and 175 °C and variations in chitosan weight with variations of 0, 1, 2 and 3 grams. The resulting biofoam product was then tested for density, water absorption, compressive strength, biodegradation and functional groups with Fourier Transform Infrared  (FTIR). Based on the results of the study, it is known that biofoam that is close to commercial standards is found in the addition of 3 gr chitosan weight with a molding temperature of 125 °C with a density value of 0.423gr/cm3, water absorption of 42.54% and compressive strength of 0.0045 Mpa. As for biodegradation, biofoam products will decompose 55.17% for 55 days in 0 g chitosan weight with a thermopressing temperature of 175 °C. The spectrum results obtained on biofoam have C-H, C-O, C-N, N-H, C=O and O-H functional groups.